Efficient Generation of Tyrosine Hydroxylase-Expressing Dopamine- Producing Neurons from Rat Peripheral Blood Progenitors Using a Combination of Growth Factors and Biomimetic Matrix - Prakash, Prabha; Rajan, Rahul; Deepti, Ayswaria; Vengellur, Ajith; Sivan, Unnikrishnan; PS, Baby Chakrapani (Archives of Clinical and Biomedical Research, 2023)
Parkinson's disease (PD) is a neurodegenerative disorder that affects dopaminergic neurons of the substantia nigra, with a prevalence of 1 in 500 individuals. Current pharmacological therapies targeting PD are shown to be ineffective in the long run, and cell therapy is contemplated as an effective therapy for PD. Allogenic cell therapies have their drawbacks as the patient depends on life-long immunosuppressants. Here, we developed a protocol for trans-differentiating the adult rat blood progenitor cells into Tyrosine Hydroxylase (TH) expressing dopamine-producing neurons using specific culture conditions for PD therapy. We identified that bFGF and CDNF, combined with a fibrin matrix, played a crucial role in the trans-differentiation process. Our results demonstrate that during trans-differentiation, the cells expressed markers for cell proliferation (Ki67), neuronal stem cell marker (Nestin), dopaminergic precursor marker (Nurr1), a dopaminergic neuronal marker (TH) and synaptophysin (Syn); a synapse formation marker in a timedependent manner. The production of Dopamine confirmed the functionality of differentiated cells by ELISA. Synaptophysin expression validates their potential to form new synapses, and TH expression confirmed by western blotting ascertains the dopaminergic neuronal lineage. This study proposed a translatable methodology for personalized cell therapy for PD patients.